Proses absorpsi Gas H2S Menggunakan Metildietanolamin - W, Ririen; Bahruddin, Bahruddin; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
H2S in the oil and gas industry is undesirable because it can lead to corrosion of pipes and equipment production. The purpose of this research is to study the effect of distance and the injection of absorbent flow rate. Absorption processes carried out continuously with free variables absorbent flow rate of 40 ml/min, 60 ml/min, 80 ml/min and 100 ml/min, with a distance of injection of 110 m, 140 m , and 170 m. The results of absorption H2S was measured by using a gas detector tube system. H2S absorption process using methyldiethanolamine as absorbent with flow rate variation of 40 ml/min is 170 ppm, absorbent flow rate of 60 ml/min is 150 ppm, absorbent flow rate of 80 ml /min and 100 ml/min which is 125 ppm . The concentration of H2S for the distance variation injection of 110 m that is 175 ppm , a distance of 140 m the injection of 150 ppm and at a distance of 170 m the injection of 125 ppm . The optimum conditions of hydrogen sulfide gas absorption process using methyldiethanolamine occurs at a flow rate of 80 ml/min at a distance of 170 m injection of H2S that can absorb as much as 58 % . The results showed that the greater the flow rate of the absorbent and absorbent injection of the longer distance, the greater the absorption of H2S gas that occurs . Keyword: absorption, corrosion, H2S, methyldiethanolamine